Assessment of knowledge, attitude, and practice towards the first aid management of foreign body aspiration and obstruction among parents of children visited SPHMMC, Addis Ababa, Ethiopia - Hailu, Yohannes; Yifru, Sisay (International Journal of Scientific Reports, 2025)
Background: Foreign body aspiration (FBA) is a leading cause of accidental death in childhood. FBs in the aerodigestive tract pose diagnostic and therapeutic challenges, contributing significantly to morbidity and mortality. Limited community awareness regarding FBA presentation and management exacerbates the problem. Few studies exist in this area, highlighting the need for further research to improve parental awareness of immediate first aid interventions and prevent delays in healthcare access. Methods: A descriptive cross-sectional study was conducted at St. Paul’s hospital millennium medical college. Data were collected from 423 parents using pretested, structured, self-administered questionnaires. SPSS version 25 was used for data analysis. Multiple logistic regression analysis identified factors associated with knowledge, attitude, and practice regarding first aid management of FBA and obstruction. Results: The 51.5% (218) of parents demonstrated adequate knowledge of FBA. Most (76.3%) had a positive attitude towards FBA first aid. 29.1% and 51.1% agreed and strongly agreed, respectively, that FBA requires immediate intervention. 17.7% (75) of parents reported a child experiencing FBA, of whom 70.7% (53) provided first aid. The majority (75.5% or 40) scored below 80% on FBA and obstruction first aid practice. Literate parents were 3.6 times more knowledgeable than illiterate parents (AOR: 3.612, 95% CI: 1.758, 7.420, p≤0.05). Conclusions: Parental knowledge and skills regarding first aid for FBA and obstruction in children are low. Educational interventions and increased awareness are crucial to reducing morbidity and mortality associated with FBA and obstruction in children.